The most efficient level of wineter protein feeding for yearling steers wintered and summer grazed on bluestem pasture. - Smith, E.F.; Cox, R.F.; Holland, L.A. (Kansas Agricultural Experiment Station, 2012)
Twenty head of good quality Hereford yearling steers, 10 head to a lot, were used in this study. They originated in southeastern Colorado and were purchased as calves in the fall of 1951 for 42 cents a pound. They were used in summer grazing tests on bluestem pasture in 1952. From November 1 until December 31, 1952, when this test started, they were on bluestem pasture supplemented with 1 pound of soybean pellets. During this test the steers were moved from pasture to pasture every 15 days to minimize any differences due to pastures. The pastures in which the steers were grazed were of such size as to vary the stocking rate from 6 to 19 acres per head. All pastures used in this winter test had sufficient grass remaining on them for winter use. although they were stocked at a normal rate for the summer of 1952.
Keywords: Beef; Protein; Yearling steers; Bluestem pasture